Factors affecting the outcome in multiple gestations - Dr Venugopal S; Dr R.B. Patil (Pediatric Review: International Journal of Pediatric Research, 2015)
Introduction: Twin births are the commonest form of multiple births. Twins have attracted considerable attention and excited curiosity from early times as a biological variety in the study of the human species. Twin pregnancy is considered as high risk pregnancy. There is poor neonatal outcome in terms of mortality and morbidity.Materials and methods: A retrospective study was conducted from Jan 2015 to Jan 2014 Mac Gann Government General Hospital. During this period there were 2643 deliveries occurred out of which 48 twins and 8 were triplets.Results: In the present study, Incidence of twin pregnancy is 18/1000 live birth. Monozygotic twinning rate is 4.2/1000 live births, while dizygotic twinning rate is 14.2/1000 live births. Perinatal mortality in twins is 177/1000 births as compared to 74.3/1000 births in singleton pregnancy i.e., 2.38 times that of singleton pregnancy. In twin pregnancy Perinatal mortality rate in 1st twin is 62.5/1000 live births while in second twin it is 114.5/1000 births. Frequency of IUGR in twin pregnancy is 85.4%. Risk of preterm labour in twin pregnancy is 64.5%. IUGR babies are more in monochorionic than in dichorionic placenta.Conclusion: Perinatal mortality in twin is higher than in of singleton pregnancy. Risk of single fetal loss (antepartum deaths) in twin pregnancy is higher than risk of both fetal losses. Perinatal mortality rate in 2st twin is double compared to first twin. Perinatal mortality increases as the gestational age decreases. Frequency of IUGR in twin pregnancy is very high and more in monochorionic than in dichorionic placenta.